2011
DOI: 10.15288/jsad.2011.72.44
|View full text |Cite
|
Sign up to set email alerts
|

Parental Awareness of Substance Use Among Youths in Public Service Sectors

Abstract: ABSTRACT. Objective: When asked about substance use, youths typically endorse higher levels of use than parents, suggesting that parents are often unaware of their child's drug and alcohol use. This study sought to examine the level of concordance between reports of youths enrolled in public sectors of care and their parents, and identify potential predictors of parental awareness of substance use and related problems. Method: Youths receiving services in one or more public sectors of care (N = 985; 67% male) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…Younger individuals often depend on their parents to recognize their symptoms and assist them into care (Dakwar et al, 2014). However, many parents are not aware of the extent and deleterious effects of substance use by their children (Green et al, 2011). Nevertheless, given the strong association of earlier age of onset with greater disorder severity and functional limitations, the lower likelihood of treatment-seeking among younger individuals represents an important challenge for health planners.…”
Section: Discussionmentioning
confidence: 99%
“…Younger individuals often depend on their parents to recognize their symptoms and assist them into care (Dakwar et al, 2014). However, many parents are not aware of the extent and deleterious effects of substance use by their children (Green et al, 2011). Nevertheless, given the strong association of earlier age of onset with greater disorder severity and functional limitations, the lower likelihood of treatment-seeking among younger individuals represents an important challenge for health planners.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such underestimation appeared to be strongly associated with higher levels of monitoring and open communication, with adolescents with better school results and who participated more in religious services, and with lower likelihood of the adolescent being involved in risk behaviors. This same result that associates high perceived monitoring and greater parental underestimation can be found in another, more recent study (Green, Bekman, Miller, Perrott, Brown, & Aarons, 2011). It emerges as especially paradoxical that greater family communication and perceived control, which should involve better knowledge of the children's substance use, leads to greater underestimation.…”
mentioning
confidence: 67%
“…The percentage of parents who consider the possibility that their children use substances increases as the child gets older, so that underestimation starts to decrease. This hypothesis can also be confirmed in one of the studies already referred to (Green et al, 2011), where 985 young people (and their parents) considered "high risk" and receiving professional support through a range of public services (judicial, social, health, school, etc. ) in San Diego, California, were interviewed to determine the accuracy of parental estimates of children's substance use, as well as to identify possible factors that predict parental knowledge of this risk behavior and of related problems.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This supports a number of earlier studies which found that educating the public on Contd... the functional impact of various medical conditions may be helpful with regard to chronic diseases such as low vision or epilepsy. [27][28][29] In the female students examined in this work, being less concerned about their own weight was a significant predictor of making a decision that favors the employee with PMS. Generally speaking, it is difficult to make decisions that go against social norms.…”
Section: Discussionmentioning
confidence: 95%